Celebration of the non-significance of Milan Kundera - Vseticka, Frantisek (Bohemica Olomucensia, 2023)
Kundera's last novel has two levels of action - French and Soviet. In the end they permeate each other. This permeation is part of the general principle of paradox. Beside the latter, Kundera in his novel applies the heptadic principle (based on number seven). The action in the novel is presented by a fictional narrator, who can be identified with the author. From the characters in the novel, also remarkable is ingot, an unknown character. The finale of the prose also contains the paradoxical principle and its framing is local. Key words: two action levels, paradoxical principle, heptadic principle, fictional narrator, ingot, paradoxical finale, local framing.